2012
DOI: 10.1371/journal.pone.0036364
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of Hafting on Paleoindian Point Variability

Abstract: It has long been argued that the form of North American Paleoindian points was affected by hafting. According to this hypothesis, hafting constrained point bases such that they are less variable than point blades. The results of several studies have been claimed to be consistent with this hypothesis. However, there are reasons to be skeptical of these results. None of the studies employed statistical tests, and all of them focused on points recovered from kill and camp sites, which makes it difficult to be cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…A follow-up analysis to the base and blade comparisons between Clovis and Folsom examined the variability between the base and the blade within the type samples. Buchanan and colleagues (2012) found that for Clovis points, basal measurements were not more variable than blade measurements. The results of our analysis agree with their finding and extend it to Folsom (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A follow-up analysis to the base and blade comparisons between Clovis and Folsom examined the variability between the base and the blade within the type samples. Buchanan and colleagues (2012) found that for Clovis points, basal measurements were not more variable than blade measurements. The results of our analysis agree with their finding and extend it to Folsom (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Judge (1973) hypothesized that the basal portion of Early Paleoindian points would be less variable than blade portions, as he assumed the latter would have been subject to resharpening. A study by Buchanan and colleagues (2012) indicated that this was not the case for Clovis points. Our results provide further support for Buchanan and colleagues’ (2012) comparison of Clovis base and blade measurements: Clovis blades are not more variable than Clovis bases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometric morphometrics analyses have also been applied in order to control the effect of potential noisy factors as size, resharpening, differences in lithic raw materials and hafting, geographical origin or distance among samples, among others (Buchanan and Collard, 2010;Castiñeira et al, 2011Castiñeira et al, , 2012Buchanan et al, 2012). Some of these works used elliptic Fourier analysis performed on the point's contour (Iovita, 2009(Iovita, , 2011, multivariate regression correction of landmark coordinate data and composite corrections involving proportions, shape, asymmetry, and size parameters (González-José and .…”
Section: Introductionmentioning
confidence: 99%
“…However, was this for portability reasons? There is no doubt that Clovis points that were clearly deposited at about the same time (if not within hours as at layer 3a at Gault, or in mammoth kills as at Lehner) varied considerably in base size and shape of the haft part (see Buchanan et al 2012). Additional testing is needed, but they seem to vary more than later fluted points that in the author's direct experience conform more to clear shape and size mental templates.…”
mentioning
confidence: 91%